Understanding speech in “noise” or free energy minimization in the soundscapes of the anthropocene - Strauss, Daniel J.; Francis, Alexander L.; Schäfer, Zeinab; Latzel, Matthias; Corona–Strauss, Farah I.; Launer, Stefan (Frontiers in Neuroscience, 2025)
Listening to speech in the presence of irrelevant sounds is ubiquitous in the modern world, but is generally acknowledged to be both effortful and unpleasant. Here we argue that this problem arises largely in circumstances that our human auditory system has not evolved to accommodate. The soundscapes of the Anthropocene are frequently characterized by an overabundance of sound sources, the vast majority of which are functionally irrelevant to a given listener. The problem of listening to speech in such environments must be solved by an auditory system that is not optimized for this task. Building on our previous work linking attention to effortful listening and incorporating an active inference approach, we argue that the answers to these questions have implications not just for the study of human audition. They are also significant for the development and broad awareness of hearing aids and cochlear implants, as well as other auditory technologies such as earbuds, immersive auditory environments, and systems for human-machine interaction.